Pengaruh Kerjasama Tim dan Komunikasi terhadap Kinerja Karyawan pada PT. BVI - Wulan Eka Permatasari; Rani Kurniasari (Universitas 45 Surabaya, 2025)
Humans are the main resource when achieving organizational success, human resources play an important contribution within an organization in achieving company goals. The aim of this research is to find out whether teamwork and communication have a significant effect on employee performance at PT. BVI and data collection by distributing questionnaires in the form of a Google form by sharing links online and techniques using a Likert scale. The population of this research is all employees at PT. BVI Landscape division and the sample in this study was 50 people using a saturated sampling technique. There are several tests carried out, namely data quality test, classical assumption test, hypothesis test and Determinant coefficient test. The tool used to process data in this research is SPSS version 25 software. This research was conducted in the period March - June 2024. This research is a quantitative research because this research was carried out in natural conditions which started by asking for research opinions and thinking patterns. It is known that partial teamwork has a positive and significant effect on employee performance and is acceptable and communication has a positive and significant effect on employee performance. Based on the test results, it can be said that the Teamwork and Communication variables together (simultaneously) have a significant effect on the Employee Performance variable at PT. BVI.